The Influence of Brand Image and Viral Marketing on Purchase Decisions of Kokumi Products in Medan Selayang District - Ida Royani; Amalia Rivana; Tohap Parulian Sihombing (Yayasan Darussalam Bengkulu, 2026)
Background: This research aims to determine the effect of brand image and viral marketing on the purchase desicion Kokumi products in Medan Selayang District. The focus of this research is to analyze how a brand is perceived by consumers and how strongly viral marketing strategies can encourage consumers to make transactions. Method: The sample in this research used purposive sampling, consisting of 100 respondents who had consumed Kokumi products at least twice. Data collection methods included interviews, questionnaires, and documentation studies. Data analysis techniques include descriptive statistics, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). Results: The results of this research show that brand image and viral marketing simultaneously have a significant effect on purchasing decisions. The tests conducted show that brand image and viral marketing partially have a positive and significant effect on purchasing decisions. The Adjusted R Square value on purchasing decisions was 0.872, meaning that 87.2% can be explained by brand image and viral marketing. Conclusion: The practical implications of this research indicate that Kokumi management can be more adapt to existing market changes, especially since the current F&B market competition is quite tight.